0711 Temporal Analysis of Chronic Musculoskeletal Pain and Sleep in Postmenopausal Women. (27th April 2018) - Frange, C; Hachul, H; Hirotsu, C; Tufik, S; Andersen, M L
Abstract: Introduction: Many postmenopausal women suffer from insomnia and chronic musculoskeletal pain, which are considered hallmarks of menopausal symptomatology. Our aim was to investigate the temporal association between chronic musculoskeletal pain and sleep in postmenopausal women in a 10-day actigraphic study. Methods: This is a microlongitudinal study in which 52 participants were allocated to 4 groups of postmenopausal women: control (CTRL, n=10), chronic musculoskeletal pain (CMP, n=12), insomnia (INS, n=15) and chronic musculoskeletal pain+insomnia (CMP+INS, n=15). All volunteers underwent a clinical interview and completed questionnaires, used an actigraph, and kept sleep diaries for 10 consecutive days. Results: CMP+INS women presented more sleep episodes (mean of 1.02 episodes) and longer sleep latency (8.97 minutes), as well as higher pain intensity during the day compared to the other groups, measured by an actigraphy. Sleep duration directly predicted pain intensity the following morning on waking (for each 1-unit increase in pain intensity, women had an increase of 6.9 minutes of sleep duration). Pain intensity at bedtime was a significant predictor of time in bed (for each 1-unit increase in pain intensity at bedtime, time in bed increased 6.7 minutes). Conclusion: The co-existence of insomnia and chronic musculoskeletal pain results in greater pain intensity and alterations in sleep homeostasis. Collectively, the data showed a bidirectional and directly proportional relationship between sleep duration and pain intensity in postmenopausal women with insomnia. This result strongly suggests that sleep and pain conditions should both be targeted in the treatment of postmenopausal women. Support (If Any): Associação Fundo de Incentivo à Pesquisa (AFIP), Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), and São Paulo Research Foundation (FAPESP, grant #2014/18722–5).